Dynamic Epigenetic Control of Highly Conserved Noncoding Elements - Seridi, Loqmane (Public Library of Science, 2014)
BACKGROUND: Many noncoding genomic loci have remained constant over long evolutionary periods, suggesting that they are exposed to strong selective pressures. The molecular functions of these elements have been partially elucidated, but the fundamental reason for their extreme conservation is still unknown. RESULTS: To gain new insights into the extreme selection of highly conserved noncoding elements (HCNEs), we used a systematic analysis of multi-omic data to study the epigenetic regulation of such elements during the development of Drosophila melanogaster. At the sequence level, HCNEs are GC-rich and have a characteristic oligomeric composition. They have higher levels of stable nucleosome occupancy than their flanking regions, and lower levels of mononucleosomes and H3.3, suggesting that these regions reside in compact chromatin. Furthermore, these regions showed remarkable modulations in histone modification and the expression levels of adjacent genes during development. Although HCNEs are primarily initiated late in replication, about 10% were related to early replication origins. Finally, HCNEs showed strong enrichment within lamina-associated domains. CONCLUSION: HCNEs have distinct and protective sequence properties, undergo dynamic epigenetic regulation, and appear to be associated with the structural components of the chromatin, replication origins, and nuclear matrix. These observations indicate that such elements are likely to have essential cellular functions, and offer insights into their epigenetic properties.